(3GdJPjjd hGdJcejd deG GSJYed ef GddaX GdONjds - (3YHO Gddg Hf CMeO Hf YHO GdYRjR Hf ehSi Hf CHj HcQ GdHTHjTj, LeGd GdOjf GdHZOGOj GdbGgQj,J (B820 (3g` s
(3ChdgG (B:s
(3Gddg (B: (3PgH Edi Cf daXI GdLdGdI eYQH , hbGd ZjQg gi daXI SQjGfjI hPgH GdLeghQ Edi CfgG daXI YQHjI , hgPG gh GdUMjM hGNJda ai gPG GdGSe Cefbhd s
(3BNQgG (B:s
(3aUd (B: (3hGdMQha GdJi Jchf efgG GdHOd ef cdGe GdYLe YTQI CMQa , hgj GdLje hGdcGa hGdHGA hGdaGA hCeG GdRGi Hbhdge ai GdfSH Edi GdQi QGRi ai dZJge HGdLje GdJi JTHg GdRGi cbhdge eQhL hQGLi s
(3eQJH Ydi MQa GdgLGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B68s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GddZIs